Terapia de aceitação e compromisso em grupo para pacientes com dor crônica - Eduardo Santos, Miyazaki (2019)
In the health system, chronic pain is one of the main causes of demand for care, from inability to work as well as for severe psychosocial and economic consequences. Drug use, the first line of treatment for chronic pain, has been linked to some negative consequences, such as opioid dependence, leading to a growing interest on psychosocial treatments. Objective: To access psychological inflexibility, pain intensity, quality of life, anxiety and depression symptoms, self-efficacy and social support of patients with chronic pain pre- and post-intervention in a group based on Acceptance and Commitment Therapy (ACT).Method: Quasi-experimental study with pre and post-test. Patients screened for the Pain Clinic, in 2017, were invited to participate in the study. Out of the 16 who agreed to participate and met the inclusion criteria, six participated in the intervention: eight sessions of 90 minutes of ACT in a group, one session per week, with pre- and post-intervention evaluation with the following instruments: Acceptance and Action Questionnaire II (AAQ-II), Brazilian version, Visual Analogue Pain Scale (EVA), SF-36 Quality of Life Inventory, Beck Anxiety (BAI) and Depression Scale (BDI), Self-efficacy Scale for Chronic Pain CPSS) and Social Support Scale (MOS). Results: The mean age of patients (3 men and 3 women) was 52,16 ± 5,63, the mean time with pain was 11,5 ± 5,78 years and five of them used morphine. After the intervention there was a reduction in psychological inflexibility (36,6 ± 5,7 pre and 18,6 ± 12,54 post), with no statistcal significance, but four out of six patients ended up below the clinical score; there was also a significant reduction in pain (p = 0,026), improvement in Quality of Life (SF-36) for the domains: Functional Capability (p = 0,003), Pain (p = 0,046), Vitality (p = 0,010), Social Aspects (p = 0,010), Emotional Aspects (p = 0,022) and Mental Health (p = 0,003); significant reduction in anxiety (BAI) symptoms (p = 0,028) and depression (BDI) symptons (p = 0,028); improvement in self-efficacy scores (p = 0,028), self-efficacy for pain management (p = 0,027), functionality (p = 0,046) and other symptoms (p = 0,028); the social support score also increased but with no statistical significance. An inverse correlation between quality of life and depression symptoms and some domains of quality of life and psychological inflexibility was found. There was no correlation between pain, anxiety and depression. Conclusion: Data shows that group based ACT intervention seems promising and should be integrated in the interdisciplairy treatment provided for Chronic Pain.